Conjuntos de bases gaussianas para K até Kr e para Pt: aplicações em cálculos de propriedades moleculares - Berredo, Ricardo Coelho de (2013)
All-electron segmented contracted quadruple zeta valence plus polarization function (QZP) basis sets for the elements from K to Xe were constructed to be used in conjunction with the non-relativistic and Douglas-Kroll-Hess (DKH) Hamiltonians. The QZP-DKH set is obtained from the corresponding original QZP basis set, i.e., the values of the contraction coefficients were re-optimized using the relativistic DKH Hamiltonian. This extends earlier works on segmented contracted QZ basis set for atoms H–Ar. At the Coupled-Cluster level of theory, the convergence of atomic ionization energy as well as of molecular spectroscopic constants as a function of basis set size is examined. Additional improvements on spectroscopic constants were achieved by applying corrections due to core-valence correlation and spin-orbit effects. This leads to estimates for the spectroscopic constants of various diatomics in gaseous phase. One verifies that the experimental and benchmark theoretical bond lengths, dissociation energies, and harmonic vibrational frequencies can be reproduced well with the QZP-DKH set. Segmented all-electron contracted double zeta valence plus polarization function (DZP) basis sets for the Pt element were constructed for use along with the non-relativistic and DKH Hamiltonians. The DZP-DKH set is loosely contracted and thus offer computational advantages compared to the generally contracted relativistic basis sets, while their sufficiently small size allows it to be used in place of effective core potentials (ECP) for routine studies of molecules. Using the one-parameter hybrid functional mPW1PW, the performance of the basis sets is assessed for predicting the molecular structures and atomic charges of platinum(II) antitumor drugs, cisplatin and carboplatin. These results can be used as reference values to calibrate further ECP calculations. Despite their compact size, the DZP sets demonstrate consistent, efficient, and reliable performance and will be especially useful in calculations of molecular properties that require explicit treatment of the core electrons. With the purpose of having a better description of electron affinity, polarizabities, and hydrogen bonding, the DZP set was augmented with diffuse (s, p, and d symmetries) and polarization (f symmetry) functions that were optimized for the anion at the Hartree-Fock and Møller-Plesset second-order levels, respectively. From optimized relativistic geometries and using non-hybrid and hybrid functionals, the performance of the augmented DZP (ADZP) set is assessed for predicting static electric dipole moment and polarizability of PtH, PtH2, and antitumor drugs (cisplatin and carboplatin). Despite its compact size, the ADZP set demonstrates consistent, efficient, and reliable performance. ADZP electric property calculations showed to be as fast as those that use augmented ECP basis sets